MEPHI’S OLYMPIADS FOR SCHOOLCHILDREN - S. E. MURAVIEV; V. I. SKRYTNYI (Высшее образование в России)
The paper focuses on the activities of the National Research Nuclear University “MEPhI” in the sphere of organization of subject Olympiads for schoolchildren. The Olympiads allow to reveal gifted schoolchildren oriented to engineering and technical specialties and showing interest in nuclear energy and high technologies. The authors dwell on the experience of the Olympiad “Rosatom”, the Engineering Olympiad for schoolchildren, the All-Russian competition of schoolchildren’s scientific works “Junior”. The examples of the emergence and the development of new Olympiads (Zvezda, Olympiad of the National Technological Initiative) are given. The paper also considers the practice of organization of short-term schools on the basis of MEPhI for winners and prize winners of the previous years Olympiads.